2019
DOI: 10.29007/8w1w
|View full text |Cite
|
Sign up to set email alerts
|

Animation notation, score distribution and AR-VR environments for spectral mimetic transfer in music composition

Abstract: This paper seeks to make a case for a compositional ideal (the mimetic transfer of a recorded or synthesized sound to the instrumental/vocal domain) which today’s technologies for animated/distributed musical notation have made more realistic than when it first appeared as a general aesthetic (with composers such as Tristan Murail and Gérard Grisey, or, in the realm of computer music, Jean-Claude Risset), simultaneously with the birth of the digital era in the 1970s. The concept of mimesis is here examined bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The aims underlying this study are to create a VE where users can immerse themselves in the visual elements of a score while listening to the corresponding music, and to help users develop a personal relationship with both the system and the score. Along a similar line, the study reported in [9] describes a system where musical notation is presented in AR to musicians wearing an HMD. In another project, Santini describes a system for creating AR gesture-based scores in the context of experimental instrumental composition [126].…”
Section: ) Compositionmentioning
confidence: 92%
“…The aims underlying this study are to create a VE where users can immerse themselves in the visual elements of a score while listening to the corresponding music, and to help users develop a personal relationship with both the system and the score. Along a similar line, the study reported in [9] describes a system where musical notation is presented in AR to musicians wearing an HMD. In another project, Santini describes a system for creating AR gesture-based scores in the context of experimental instrumental composition [126].…”
Section: ) Compositionmentioning
confidence: 92%